Pengaruh Globalisasi terhadap Minat Generasi Muda dalam Melestarikan Kesenian Tradisional Indonesia - Amalia, Riska; Shifa, Laila Nur; Fadilah, Ahmad Arif (Lembaga Yasin AlSys, 2025)
Globalization is an event that causes many changes in all aspects of people's lives, especially the younger generation. The ease of obtaining information changes the mindset of the younger generation to become more modern. This can affect the interest of the younger generation in preserving Indonesian traditional arts. Therefore, this paper aims to describe the influence of modernization on the interest of the younger generation in preserving Indonesian traditional arts in the era of globalization. This research is descriptive and qualitative. The data collection method is literature study by collecting various references, both primary and secondary sources that are relevant to the younger generation and traditional arts in the era of globalization. The results of the research study show that the current of globalization greatly affects the lives and mindsets of young people to become more modern, this thinking makes some of them think that something traditional like traditional arts is something ancient so that their interest in and interest in traditional arts begins to decrease and begin to forget about traditional arts. Another factor is the large number of young people who consider arts from foreign countries to be better and more interesting than traditional Indonesian arts, and also their lack of awareness of the importance of maintaining traditional arts, which is Indonesia's national identity.